2016
DOI: 10.1177/1043986216673010
|View full text |Cite
|
Sign up to set email alerts
|

Exoneree Engagement in Policy Reform Work

Abstract: Through a lens of resilience and growth alongside continuing distress, this exploratory research study examines a convenience sample of exonerees and innocence movement personnel who are engaged in the policy reform process to understand how exoneree involvement may change exonerees themselves, the innocence movement, and possibly the criminal justice system. Data were collected through prequestionnaires and semi-structured interviews, supplemented with archival material, and analyzed using a narrative approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Peer support groups provide one avenue for exonerees to share lived experiences with others who can uniquely empathize (DeShay, 2016; Wildeman et al, 2011). In DeShay (2016), exonerees explained that regular meetings with fellow exonerees benefited their coping process by providing camaraderie as well as advice on how to navigate postrelease obstacles—but while sharing their experiences may be healing for some, it may prove retraumatizing for others (Konvisser & Werry, 2017). Further, of the three sources of social support measured in the current study, family support was the only source to correlate with both PTSD symptoms and depressive symptoms, suggesting the importance of involving exonerees’ families in treatment as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peer support groups provide one avenue for exonerees to share lived experiences with others who can uniquely empathize (DeShay, 2016; Wildeman et al, 2011). In DeShay (2016), exonerees explained that regular meetings with fellow exonerees benefited their coping process by providing camaraderie as well as advice on how to navigate postrelease obstacles—but while sharing their experiences may be healing for some, it may prove retraumatizing for others (Konvisser & Werry, 2017). Further, of the three sources of social support measured in the current study, family support was the only source to correlate with both PTSD symptoms and depressive symptoms, suggesting the importance of involving exonerees’ families in treatment as well.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, self-blame was unrelated to symptoms of PTSD or depression—and in fact, self-blame was rather low in our sample overall. This may reflect exonerees’ unique understanding that wrongful conviction can happen to anyone—and indeed, that is a common sentiment among exonerees (Konvisser, 2015), especially in advocating for criminal justice reform (Konvisser & Werry, 2017). However, exonerees who expressed stronger negative cognitions about the self (e.g., “I have no future”) and/or world (e.g., “People cannot be trusted”) tended to report stronger symptoms of PTSD and depression and weaker social support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some American exonerees have taken on this task by using their financial compensation to create exoneree led advocacy organizations in their state, or working with existing innocence organizations to raise awareness of the problems they face, and share their experiences. Konvisser and Werry (2017) conducted qualitative interviews with five exonerees who engaged in policy reform work and found that exonerees were motivated to educate the public, raise awareness, and advocate for others who have been wrongfully convicted, sentiments echoed by the exonerees we interviewed.…”
Section: Discussionmentioning
confidence: 99%
“…In this portion of the book, the author discusses the background of the advocates that joined the fight to combat wrongful conviction. According to Konvisser and Werry (2017), individuals are participating in such activities of reform in order to engage an active example of how to correct injustice. Norris asserts that about three-fourths of cases submitted to innocence organizations are turned down, but the important element that roots the movement are the narratives that are involved with each case that is accepted.…”
mentioning
confidence: 99%